PARTISIPASI DAN PERSEPI ORANG TUA SISWA DALAM MITIGASI DAMPAK PENCEMARAN TIMBEL (Pb) DI UDARA - Ridwan Fauzi; Muhamad Yusup Hidayat; Bambang Hindratmo; Siti Masitoh (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2019)
Lead pollution (Pb) as a negative impact of battery smelting has a bad effect on human health. Children are at the greatest risk as a result of the lead pollution. Involvement of parents in carrying out mitigation efforts to reduce the impact of air pollution is important to be improved. This study aims to determine perception, participation, and factors affecting the parents of the students in mitigating the impact of lead pollution. The respondents of the study using survey methods are are parents of the students at Madrasah Ibtidaiyah Baitussa’adah, Curug, Tangerang. The data was analyzed by using the Likert scale, scoring, and logit regression analysis. The data were collected from 174 respondents. Result from Likert analysis showed that in general the parents of the students had a good understanding related to the lead pollution in the air. The majority or 69% of the respondents have a moderate level of participation in mitigating the effects of lead pollution in the air. Furthermore, the research results also showed that the willingness of the community to carry out mitigation actions was influenced by family income, knowledge on lead pollution, as well as length of time for activities carried out outside the home. Mitigation actions against lead pollution in the need to be done by the community, especially by the parents of the students.